2007
DOI: 10.1111/j.1574-6968.2007.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five rep-PCR genomic fingerprinting methods for differentiation of  fecalEscherichia colifrom humans, poultry and wild birds

Abstract: The development of a methodology to identify the origin of fecal pollution is important both for assessing the degree of risk posed to public health and for developing strategies to mitigate the environmental loading of pathogens associated with waterborne disease transmission. Five rep-PCR genomic fingerprinting methods, such as rep-PCR, enterobacterial repetitive intergenic consensus (ERIC)-PCR, ERIC2-PCR, BOX-PCR and (GTG)(5)-PCR, were assessed for their potential in differentiation of 232 fecal Escherichia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
1
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 22 publications
4
75
1
9
Order By: Relevance
“…ERIC-PCR is effective in typing E. coli isolates from animals (Mohapatra, Broersma, Mazumder, 2007;Prabu et al, 2010;Wan et al, 2011;De la Fé Rodriguez et al, 2012) and water (Casarez, Pillai, Di Giovanni, 2007). However, some reports indicated that ERIC-PCR is not effective in typing E. coli isolated from humans, animals, and food (Giammanco et al, 2002;Leung et al, 2004;Costa et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…ERIC-PCR is effective in typing E. coli isolates from animals (Mohapatra, Broersma, Mazumder, 2007;Prabu et al, 2010;Wan et al, 2011;De la Fé Rodriguez et al, 2012) and water (Casarez, Pillai, Di Giovanni, 2007). However, some reports indicated that ERIC-PCR is not effective in typing E. coli isolated from humans, animals, and food (Giammanco et al, 2002;Leung et al, 2004;Costa et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Also, (GTG) 5 -PCR was tested for its ability to track the origins of E. coli, Lactobacillus spp., and Enterococcus spp. isolated from various sources (12,24,25,39). We propose an improved PCR methodology that employs an N 6 (CGG) 4 primer with a high annealing temperature.…”
mentioning
confidence: 99%
“…DNA fingerprinting of EAST1-EC serotype O15 was performed using enterobacterial repetitive intergenic consensus (ERIC) 2-PCR and BOX-PCR using ERIC2 and BOX-A1R primers, respectively [21]. PCR was performed in a 25-μL reaction mixture containing 0.2 μM of each primer, 0.2 mM dNTPs, 1× GoTaq DNA polymerase buffer, 3.0 mM MgCl 2 , 1.25 U GoTaq DNA polymerase, and 50 ng of DNA template (prepared using glass fiber matrix spin column; Geneaid, Taiwan).…”
Section: Dna Fingerprintingmentioning
confidence: 99%